2017
DOI: 10.1016/j.ejcb.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in S-adenosylhomocysteine hydrolase (AHCY) affect its nucleocytoplasmic distribution and capability to interact with S-adenosylhomocysteine hydrolase-like 1 protein

Abstract: S-adenosylhomocysteine hydrolase (AHCY) is thought to be located at the sites of ongoing AdoMet-dependent methylation, presumably in the cell nucleus. Endogenous AHCY is located both in cytoplasm and the nucleus. Little is known regarding mechanisms that drive its subcellular distribution, and even less is known on how mutations causing AHCY deficiency affect its intracellular dynamics. Using fluorescence microscopy and GFP-tagged AHCY constructs we show significant differences in the intensity ratio between n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…6b and Supplementary Table 1, there were 123 proteins were specifically identified in the biotin-treated BirA*-DJ-1 cells. Among these proteins, SAHH-like protein (AHCYL) caught our attention, not only because it ranked in the top ten based on the scores generated by analytic software, but also because it plays a dominant negative role in the regulation of SAHH activity 31,32 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6b and Supplementary Table 1, there were 123 proteins were specifically identified in the biotin-treated BirA*-DJ-1 cells. Among these proteins, SAHH-like protein (AHCYL) caught our attention, not only because it ranked in the top ten based on the scores generated by analytic software, but also because it plays a dominant negative role in the regulation of SAHH activity 31,32 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been documented that SAHH functions as a tetramer with the cofactor NAD + /NADH bound to each subunit, and the heteromultimerization of AHCYL and SAHH can decrease SAHH activity 31,32 . Thus, we hypothesized that DJ-1 changes the formation of heteromultimers of AHCYL (AHCYL1 or AHCYL2) and SAHH, and then impacts the tetramerization of SAHH.…”
Section: Resultsmentioning
confidence: 99%
“…One finding relates to inhibition of N 6 -methyladenosine mRNA methylation that was shown to lengthen the mammalian circadian period in vitro and in vivo (61,62). On the other hand, AHCY was shown to be localized in the nucleus in Arabidopsis, Xenopus laevis, and mammalian cells (27,(63)(64)(65)(66), suggesting that localized activity of AHCY at specific sites may promote activity of HMTs that would otherwise be inhibited by SAH. Nicely paralleling our study, AHCY was shown to be enriched at TSS of transcriptionally active genes marked with H3K4me3, including several circadian genes (26).…”
Section: Discussionmentioning
confidence: 99%
“…This is the case of AHCY, whose β-hydroxybutyrylation decreases its enzymatic activity, demonstrating a functional relevance of the modification. In addition to the sites directly affecting activity, AHCY was modified at two additional sites in the N-terminal domain, which we hypothesize could affect protein-protein interactions or subcellular localization of AHCY (Grbesa et al, 2017). Future studies will help define the full array of functional consequences of Kbhb on target proteins and whether, as observed for AHCY, Kbhb targets other metabolic enzymes in a similar manner.…”
Section: Discussionmentioning
confidence: 84%
“…To do so, we examined the crystal structure of AHCY in its NAD + -bound form ( Figure 5A). AHCY functions as a tetramer, comprised of two homodimers of structurally identical ~48-kDa subunits that each contain a substrate binding domain, cofactor binding domain and C-terminal loop (Grbesa et al, 2017). NAD + binding to AHCY depends on the interaction between Cterminal loops of neighboring subunits, which together constitute one cofactor binding and substrate binding site (Wang et al, 2014).…”
Section: Kbhb Of Lysines Within the Nad + Binding Interface Of Ahcy Imentioning
confidence: 99%